The differences of muscle activation in forehand serve-receiving technique of male tennis players at different skills. - Yuxin Zhang; Jiajie Tian; Zhouye Chen (PLoS ONE)
The purpose of this study was to analyze differences in muscle activation of the right upper limb and part of the trunk and differences in stroke performance of forehand receiving in male tennis players of different levels of performance at different serve speeds. Thirty male tennis players (no difference in age, height, weight) were divided into senior (AG, n=15) and intermediate (IG, n=15) groups to perform 6 forehands receive tests at 2 serve speeds: low-speed serve (130-140km/h), high-speed serve (160-170km/h). Muscle activity from the right of biceps brachii (BB), triceps brachii (TB), brachioradialis (BC), deltoid (DT), trapezius (TP), pectoralis major (PM), obliquus externus abdominis (OEA) and latissimus dorsi (LD) were recorded using surface electromyography during the concentric phase of the lift and expressed as a percentage of each muscle's maximal activity, recorded during a maximal isometric contraction. Returned speed and placement were recorded using a high-speed camera. The results showed that the AG had significantly lower muscle activity (p < 0.05) in the backswing, impart, follow-through phases of the receive and more consistent dominant muscles in all phases, while the opposite was true for the IG. At both serve speeds, AG had significantly faster ball speeds (p < 0.05) and higher placement scores (p < 0.05) compared to IG. It is important to develop the athlete's receive action at lower muscle activation and higher joint kinetic energy, which may be an important way to improve receive performance in a short period.